Optimal predictive low glucose management settings during physical exercise in adolescents with type 1 diabetes. Issue 1 (22nd November 2018) - Cherubini, Valentino; Gesuita, Rosaria; Skrami, Edlira; Rabbone, Ivana; Bonfanti, Riccardo; Arnaldi, Claudia; D'Annunzio, Giuseppe; Frongia, Annapaola; Lombardo, Fortunato; Piccinno, Elvira; Schiaffini, Riccardo; Toni, Sonia; et al.
Abstract : Objectives: To assess the optimal setting of the predictive low glucose management (PLGM) algorithm for preventing exercise‐induced hypoglycemia in adolescents with type 1 diabetes. Methods: Thirty‐four adolescents, 15 to 20 years, wearing PLGM system, were followed during 3 days exercise during a diabetes camp. PLGM threshold was set at 70 mg/dL between 8am and 10pm and 90 mg/dL during 10pm and 8am Adolescents were divided into group A and B, with PLGM threshold at 90 and 70 mg/dL, respectively, during exercise. Time spent in hypoglycemia and AUC for time slots 8am to 1pm, 1 to 4pm, 4 to 11pm, 11pm to 3am, 3 to 8am, in 3 days were compared between groups by Wilcoxon rank sum test. Results: We analyzed 31 patients (median age 15.0 years, 58.1% males, median diabetes duration 7.0 years, hemoglobin A1c [HbA1c] 7.1%). No significant difference has been observed in time spent in hypoglycemia between groups using threshold 70 or 90. Time spent in target was similar in both groups, as well as time spent in hypo or hyperglycemia. The trends of blood glucose over the 3 days in the 2 groups over‐lapped without significant differences. Conclusions: A PLGM threshold of 90 mg/dL during the night was associated with reduced time in hypoglycemia in adolescents doing frequent physical exercise, while maintaining 65.1% time in range during the day. However, a threshold of 70 mg/dL seems to be safe in the duration of the physical exercise. PLGM system in adolescents with type 1 diabetes was effective to prevent hypoglycemia during and after exercise, irrespective of the PLGM thresholds used.